A STUDY ON THE COMMUNICATION STRATEGIES EMPLOYED BY GRADE 10 STUDENTS IN THANG LONG HIGH SCHOOL, HA NOI TO BUILD AND LEARN VOCABULARY IN COMMUNICATION TASKS IN SPEAKING LESSONS - Đỗ, Thị Phương Thảo (2020)
Normally, people often believe that rich vocabulary can only be found in extensive reading or writing. However, another potential source of vocabulary that should be put under consideration is communication tasks in speaking skill lessons. When conducting communication tasks, students are forced to use communication strategies which help them build and learn new words. Therefore, this research aims to find out the communication strategies students employ to learn new words in communication tasks with their partners as well as the teacher. Through it, some suggestions to build rich vocabulary in communication tasks are expected to be given out. To collect data for the study, survey questions were delivered to fifty 10th form students specializing in English in Thang Long high school. Besides, interviews were also adopted to five teachers teaching English to the 10th form for their opinions. Observations were taken place in two classes to gain more in-depth information.